Surgical mask wearing behaviour in COVID-19 pandemic and influenza seasons: a cross-sectional study on healthcare professional students and staff's perspective in Southern California. Issue 10 (11th October 2022) - Lui, Kin Long; Daher, Noha; López, David; Kim, Veronica; Tan, Laren; Cohen, Pamela Monterroso; Alismail, Abdullah
Abstract : Objective: To investigate healthcare professional staff and students' perception of wearing surgical masks before and after their experience with the COVID-19 pandemic, and to evaluate the impact on mask wearing behaviour in future influenza seasons. Design: Cross-sectional study using anonymous survey. Setting and participants: Healthcare students and staff from a healthcare academic institution in Southern California participated in the mask survey study. Survey results were collected from June to November 2021. A total of 305 respondents responded to the survey, with 173 being healthcare students and 132 being working healthcare staff. Outcomes: The study examined respondents' perceptions and hospital mask wearing behaviour before and after their COVID-19 pandemic experience, as well as during previous and future influenza seasons. Results: Two hundred and sixty-four (86.6%) respondents agreed that wearing a surgical mask reduces infection and limits transmission of infectious disease, yet prior to the pandemic, only a small proportion wore a mask in the hospital or during patient care. After experiencing the COVID-19 pandemic, more respondents indicated that they would continue to wear a mask when they are in a hospital in general (n=145, 47.5%), during patient care (n=262, 85.9%), during influenza seasons throughout the hospital (n=205, 67.2%) and during influenza seasons during patient care (n=270, 88.5%). Conclusion: The pandemic experience has greatly influenced the health prevention behaviours of healthcare students and staff. After the pandemic, many respondents will continue to practice surgical mask wearing behaviour in the hospital, especially during face-to-face patient care. This demonstrates a significant change in health prevention perceptions among the current and the future generation of healthcare professionals.